Scholarship of Application: When Service Is Scholarship - A Workshop for Medical Educators - Linda Tewksbury; Robin English; Cynthia Christy; Joseph Gigante; Antoinette Spoto-Cannons; Nasreen Talib; Janice Hanson (Association of American Medical Colleges, 2009)
Abstract This resource is a workshop designed for health care educators interested in advancing their scholarship in medical education. The goal of this workshop is to provide participants with practical guidance for turning their educational service into scholarship. Through this workshop, participants will develop a firm understanding of the scholarship of application, one of the four types of scholarship outlined by Ernest Boyer in 1990. The scholarship of application involves service and the use of knowledge to solve problems of individuals or society. Examples of applying knowledge in medical education include curriculum development, clerkship restructuring, and development and implementation of evaluation tools or new programs. While medical educators typically engage in these activities, many do not recognize that such activities have the potential to qualify as scholarship. Participants in this workshop will have the opportunity to go through the process of moving an educational project through the steps necessary for it to qualify as high-quality scholarship, based on Glassick's six characteristics of scholarship. Finally, participants will have the opportunity to apply the characteristics of scholarship to their own educational endeavors and discuss opportunities for the dissemination of such work. Nearly all participants in the workshop rated it excellent in delivery, content, objectives met, interactivity, and overall effectiveness. Comments on the peer review feedback form indicated that the participants especially appreciated the systematic analysis of the concepts of scholarship of application as well as the time to discuss, reflect, and apply these concepts to specific examples so they could develop ideas for their own projects.